2022
DOI: 10.3389/fonc.2021.802188
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Circulating Tumor Cells and Circulating Endothelial Cells in Predicting Bladder Cancer Prognosis and Neoadjuvant Chemosensitivity

Abstract: PurposeTo investigate the role of circulating rare cells (CRCs), namely, circulating tumor cells (CTCs) and circulating endothelial cells (CECs), in aiding early intervention, treatment decision, and prognostication in bladder cancer.MethodsA total of 196 patients with pathologically confirmed bladder cancer, namely, 141 non-muscle invasive bladder cancer (NMIBC) and 55 muscle invasive bladder cancer (MIBC) patients. There were 32 patients who received cisplatin-based neoadjuvant chemotherapy (NAC) followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Liquid biopsy has been widely explored in recent years because of its convenience and low invasiveness. Circulating tumour DNA (ctDNA) and circulating tumour cells (CTCs) have great potential in predicting the efficacy of NAC in MIBC patients [11,12], and our previous study also confirmed the value of CTCs in predicting NAC sensitivity [13].…”
supporting
confidence: 67%
“…Liquid biopsy has been widely explored in recent years because of its convenience and low invasiveness. Circulating tumour DNA (ctDNA) and circulating tumour cells (CTCs) have great potential in predicting the efficacy of NAC in MIBC patients [11,12], and our previous study also confirmed the value of CTCs in predicting NAC sensitivity [13].…”
supporting
confidence: 67%
“…Based on the SE-iFISH strategy, Yang et al demonstrated that patients with early bladder cancer had more triploid CTCs, tetraploid CTCs, and total circulation endothelial cells (CECs). Various CTC/ CEC subtypes may have di erent potential function to guide the diagnosis, prognosis prediction, and treatment decision of bladder cancer [92]. Li et al found that the presence of circulating tumor-cell-associated white blood cell (CTC-WBC) clusters is an independent prognostic factor for advanced non-small-cell lung cancer [93].…”
Section: Negative Sorting Methodsmentioning
confidence: 99%
“…The density of lymphatic vessels corelated with higher pT stage, higher grade and sessile growth patterns. It has been also detected that circulating endothelial cells (CECs) is associated with higher tumour stage and grade [ 104 ].…”
Section: The Non-immune Components Of the Tumour Microenvironmentmentioning
confidence: 99%